A comprehensive study to evaluate the wound healing potential of okra (Abelmoschus esculentus) fruit. (6th April 2022) - Sipahi, Hande; Orak, Duygu; Reis, Rengin; Yalman, Kübra; Şenol, Onur; Palabiyik-Yücelik, Saziye Sezin; Deniz, İnci and Algül, Derya and Guzelmeric, Etil and Çelep, M. Engin and Argin, Sanem and Özkan, Ferda and Halıcı, Zekai and Aydın, Ahmet and Yesilada, Erdem
Abstract: Ethnopharmacological relevance: Okra fruit ( Abelmoschus esculentus (L.) Moench) has been extensively used for the treatment of skin damage and subcutaneous tissue abscess for many years in Turkish folk medicine. Aim of study: In this study, we aimed to investigate the wound healing potential of okra fruit by in vitro and in vivo experimental models in detail. Furthermore, based on the results of experiments, a wound healing formulation was developed and its activity profile was studied. Materials and methods: For this purpose, the phenolic, flavonoid and proanthocyanidin contents and chemical profile of aqueous and ethanolic extracts prepared from okra fruits cultivated in two different locations of Turkey, i.e. Aegean and Kilis regions, were comparatively determined and the tryptophan levels, which is known to be an influential factor in wound healing, were measured. Antioxidant activity of the okra fruit extracts was determined by DPPH test, ABTS radical scavenger activity, iron-binding capacity, total antioxidant capacity and copper reduction capacity assays. Moreover, antibacterial activity potentials of the aqueous and ethanolic extracts of okra fruits were determined. The protective effect of the extracts against H2 O2 -induced oxidative stress and anti-inflammatory activity were assessed in HDF (human dermal fibroblast) cells and in RAW 264.7 murine macrophages, respectively. The biocompatibility of the gel formulations prepared with the best performing extract were evaluated by human Epiderm™ reconstituted skin irritation test model. Wound-healing activity was investigated in rats by in vivo excision model and, histopathological examination of tissues and gene expression levels of inflammation markers were also determined. Results: According to our findings, the aqueous and ethanolic extracts of okra fruits were found to possess a rich in phenolic content. Besides, isoquercitrin was found to be a marker component in ethanolic extracts of okra fruits. Both extracts exhibited antioxidant activity with significant protective effect against H2 O2 -induced damage in HDF cells by diminishing the MDA level. Also, the highest dose of ethanolic extracts has displayed a potent anti-inflammatory activity on LPS-induced RAW264.7 cells. Besides, both water and ethanolic extracts were shown to possess antimicrobial activity. On the other hand, the formulations prepared from the extracts were found non-irritant on in vitro Epiderm™-SIT. In vivo excision assay showed that tissue TGF-β and IL-1β levels were significantly decreased by the 5% okra ethanolic gel formulation. The histopathological analysis also demonstrated that collagenisation and granulation tissue maturation were found higher in 5% (w/v) okra ethanolic extract-treated group. Conclusion: 5% of okra ethanolic extract might be suggested as a potent wound healing agent based on the antimicrobial, antioxidant and anti-inflammatory tests. The proposed activity was also confirmed by the histopathological findings and gene expression analysis. Graphical abstract: Image 1